Flow control of the wake vortex street of a circular cylinder by using a traveling wave wall at low Reynolds number. (2nd March 2017) - Xu, Feng; Chen, Wen-Li; Bai, Wei-Feng; Xiao, Yi-Qing; Ou, Jin-Ping
Highlights: CFD simulation is employed to carry out the entire procedure from FR to the TWW. Influences of the TWW propagation direction and the wave velocity are investigated. TWW in the "Downstream" direction eliminates the oscillating wake of the cylinder. Fluctuating value of the lift coefficient plummets to minimum value at c/U∞ = 2.0. Mechanism of the TWW method is expounded by the BVF and the relative flow fields. Abstract: In the present study, a traveling wave wall (TWW) was employed to manipulate the vortex shedding behind a fixed circular cylinder based on a 2-D CFD numerical simulation method at a low Reynolds number of 200. The study mainly focused on four types of TWW propagation directions combined with nine different wave velocities to eliminate vortex shedding, and the lift and drag coefficients and vortex shedding modes at different propagation directions or velocities were analyzed in detail to access the effectiveness of the TWW flow control method. The control mechanism of eliminating wake stemming from the flow around a TWW-controlled circular cylinder was revealed by the boundary vorticity flux (BVF) and relative flow fields. The results show that the type of downstream propagating TWW can effectively eliminate the alternating wake. When the ratio of the wave velocity to the oncoming velocity is 2.0, the fluctuations of the lift coefficients descended to the lowest point. The averages of the drag coefficients decreased with increasing wave velocity and descended to the lowest point when the ratio of the wave velocity to the oncoming velocity was 5.0. Owing to the capture of small-scale vortices, there was a relatively larger level of vorticity in the wave valley of the TWW cylinder. The relative flow fields showed that the vortex shedding from the cylinder was completely eliminated and that the goal of eliminating the oscillating wake and suppressing the potential vortex-induced vibration (VIV) of flow around a cylinder was achieved.